ANALISIS JENIS DAN KANDUNGAN LOGAM PADA BATUAN BUANGAN DARI PERTAMBANGAN EMAS POBOYA - Rika Rahayu; Paulus Hengky Abram (Media Eksakta, 2020)
Metals has an important role for human life, especially in the industrial field. The purpose of this research is to find out the metal type and content in waste rock from the Poboya gold mine. The sampling technique is done by grabbing sampling, which is to take a lump of rock at a mining site. The analytical method used to determine the content and percentage of elements in rocks is XRF (X-Ray Fluorescence) spectrophotometry. The analysis results show that the metals contained in the waste rock from Poboya gold mining are Silicon (Si), Iron (Fe), Potassium (K), Aluminium (Al), Calcium (Ca), Titanium (Ti), Arsenic (As), Zirconium (Zr), Manganese (Mn), Strontium (Sr), Barium (Ba), Rubidium (Rb), Zinc (Zn), Niobium (Nb), Indium (In), Tin (Sn) and Stibium/Antimony (Sb). The highest percentage metals are Silicon 52.98% and Iron 23.56%. Based on these results, the high content of silica oxide and iron oxide in waste rock from Poboya has the potential as a basis to be used for making nano materials, especially nano silica and ferromagnetic materials.